Potensi Jangkauan Wisata Harian Berdasarakan Analisis Network Sistem Informasi Geografis: Studi Kasus Kabupaten Hulu Sungai Utara - Boby Rahman (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2021)
Hulu Sungai Utara Regency has a tourism mainstay of the province, swamp buffalo, which has attracted many national and international tourists. As one of the great tourist magnets, swamp buffalo tourism is not yet supported by other attractions, so tourists tend to only visit one object and leave immediately. Hulu Sungai Utara Regency has other potential tourism objects, but with a wide landscape and not optimal tourism conditions, it is necessary to plan tourism routes with daily reach. This research uses quantitative methodology with network analysis and application assistance of ArcGIS, finding the optimum route as the basic daily reach of travel. As a result, analysis of the optimum route selection results in the main tourist area as a tour package from a collection of all tourist themes (natural, religious, historical, cultural and shopping) that can be reached by a tour package for 2 days, while tourism with a natural theme can be taken 1 day by 3 package options, as well as religious tourism that can be reached within 1 day